2021
DOI: 10.1002/prot.26161
|View full text |Cite
|
Sign up to set email alerts
|

Physics‐based protein structure refinement in the era of artificial intelligence

Abstract: Protein structure refinement is the last step in protein structure prediction pipelines.Physics-based refinement via molecular dynamics (MD) simulations has made significant progress during recent years. During CASP14, we tested a new refinement protocol based on an improved sampling strategy via MD simulations. MD simulations were carried out at an elevated temperature (360 K). An optimized use of biasing restraints and the use of multiple starting models led to enhanced sampling. The new protocol generally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 75 publications
(173 reference statements)
2
20
0
Order By: Relevance
“…Some consideration of potential future changes can be found elsewhere in this issue. 30,31 In conclusion, we have shown that the reLLG is a useful addition…”
Section: Relevance Of Refinement Category In Caspmentioning
confidence: 63%
See 1 more Smart Citation
“…Some consideration of potential future changes can be found elsewhere in this issue. 30,31 In conclusion, we have shown that the reLLG is a useful addition…”
Section: Relevance Of Refinement Category In Caspmentioning
confidence: 63%
“…Although the best refinement groups were consistently able to improve the server‐generated refinement targets, most refinement methods degrade the AlphaFold2 models, as seen here for MR as well as for other CASP assessment measures. 30 This is in spite of the lack, in the AlphaFold2 algorithm, 10 of the explicit physics‐based knowledge employed by the most successful refinement groups (e.g., Heo et al 31 ). Figure 12 shows that, with one marginal exception (a slight improvement on an AlphaFold2 starting model), the AlphaFold2 model would have scored equal or higher on the reLLG score compared to the best refined model, even including the double‐barrelled targets starting from AlphaFold2 models.…”
Section: Discussionmentioning
confidence: 99%
“…S6). However, one should be careful with simulations using AI-based structural models, since their conformation may be kinetically trapped into a specific state, inhibiting the study of conformational changes [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, we modeled the structures of 25 FM/TBM and TBM-hard targets of CASP14. The average TM-score and lDDT score of the models were compared with those of the following server groups: FEIG-S [ 36 ], BAKER-ROSETTASERVER [ 37 ], Zhang-Server, and QUARK [ 38 ]. The model structures of the other groups were downloaded from the archive of the CASP14 website, and TM-score and lDDT scores were recalculated with the crystal structures and domain information for a fair comparison.…”
Section: Resultsmentioning
confidence: 99%